Novel quinolinyl-thiazole hybrid candidates bearing N-methyl piperazine as potential anti-breast cancer agents: synthesis, biological evaluation and computational studies - Dhongade, Archana B.; Shah, Umang; Patil, Bhausaheb N.; Shinde, Rahul A.; Sarkar, Ruma; Mukherjee, Adrija; Mali, Suraj N.; Adole, Vishnu A.; Pawar, Thansing B. (RSC Advances, 2025)
Breast cancer remains one of the most pressing global health concerns, emphasizing the urgent need for novel and effective therapeutic strategies. In this context, a new series of quinolinyl-thiazole derivatives incorporating an N-methyl piperazine moiety (6a-6h) was rationally designed, synthesized, and thoroughly characterized using FT-IR, 1H NMR, 13C NMR, and mass spectral methods. The anti-breast cancer potential of these compounds was assessed against the triple-negative breast cancer cell line MDA-MB-231, exhibiting IC50 values ranging from 1.415 +/- 0.16 to 2.898 +/- 0.27 mu M, thus highlighting their anti-breast cancer potential. Within the series, compound 6a showed the highest potency with the lowest IC50 value, whereas 6f displayed the weakest activity. Molecular docking of quinolinyl-thiazole derivatives (6a, 6f, 6g and 6h) against epidermal growth factor receptor tyrosine kinase revealed binding affinities correlating with their in vitro cytotoxicity on MDA-MB-231 cells, with 6a showing the strongest activity (IC50 = 1.415 +/- 0.16 mu M; docking score = -10.0 kcal mol-1) via key hydrogen bonds, electrostatic contacts, and hydrophobic interactions. Furthermore, in silico ADME evaluation and drug-likeness analysis indicated that all synthesized derivatives possessed favorable pharmacokinetic properties. Density functional theory analysis of the most potent compound (6a) offered valuable insights into its structural characteristics, electronic distribution, and chemical reactivity via optimized geometry, frontier molecular orbital and molecular electrostatic potential surface studies. The results suggested that the synthesized compounds are promising candidates for further investigation.